CPU Thread Prioritization Using a Dynamic Quantum Time Round-Robin Algorithm - Mohammed, Maysoon A.; Mazlina, Abdul Majid; Balsam, A. Mustafa; Ghani, Rana Fareed (Asian Research Publishing Network, 2016)
In Round-Robin Scheduling, the time quantum is fixed and processes are scheduled such that no process uses CPU time more than one time quantum in one go. If time quantum is too large, the response time of the processes will not be tolerated in an interactive environment. If the time quantum is too small, unnecessary frequent context switch may occur. Consequently, overheads result in fewer throughputs. In this study, we propose a priority Round-Robin algorithm with dynamic quantum time (PDQT). The algorithm used the old fixed quantum time to generate new one for each process depending on its priority. The simple Round-Robin algorithm has been improved by about 20%. By controlling quantum time, we experience fewer context switches and shorter waiting and turnaround times, thereby obtaining higher throughput.